CORPORATE SIZE IN MODERATE THE INFLUENCE OF CURRENT RATIO AND DEBT TO EQUITY RATIO ON INCOME SMOOTHING - Nariman, Augustpaosa; Hastuti, Rini Tri; Flolinda, Karin; Sefika, Salva (Graduate Program of Universitas Tarumanagara, 2025)
Net profit information is very important for the sustainability of the corporate's operational activities and investor confidence in investing their funds, so that corporate management practices income smoothing or income smoothing by manipulating the corporate's financial statements. Several previous studies, there are gaps in experiment outcomes from one experimenter to another, so this study tries to re-examine the gaps or gaps found in several studies. This study is a replication study to re-examine several factors that influence income smoothing by using Corporate size as a moderating instrument variable. The addition of this moderation instrument variable aims to increase the depth of analysis and provide a more nuanced understanding of the relationship between the dependent instrument variable and the independent instrument variable. Moderating instrument variables can strengthen the relationship between the two instrument variables. The purpose of this study is to determine the effect of the current ratio and debt to equity ratio on income smoothing with corporate size as a moderating instrument variable in manufacturing corporates listed on the Indonesia Stock Exchange for the period 2020-2022. This study uses a purpose sampling technique with data for three years obtained from the website www.idx.co.id. Data processing in this study used SPSS version 27 and Microsoft Excel 2016 applications. The analysis in this study used logistic regression analysis for the current ratio and debt to equity ratio hypotheses and absolute difference analysis for the current ratio and debt to equity ratio on income smoothing with corporate size as a moderating instrument variable. The outcomes of this study indicate that the current ratio and debt to equity ratio do not affect income smoothing. Corporate size as a moderating instrument variable cannot moderate the current ratio and debt to equity ratio instrument variables on income smoothing.